Social Media as a Virtual Public Sphere in Health Education: A Systematic Review from the Perspective of Habermas' Public Sphere Theory - Nangi, Mohamad Guntur; Kamaruddin, Syamsu A; Adam, Arlin; Lestari, Sari Arie (Al-Hijrah Indonesia, 2024)
Social media has become an important platform in health education. It allows individuals to connect and share information about health. However, no studies have systematically explored the role of social media as a virtual public space in health education. This systematic review aims to explore the role of social media as a virtual public sphere in health education, from the perspective of Habermas' public sphere theory. The review was conducted by searching for research articles published in reputable scientific journals between 2010 and 2023. The method used to write this article is a systematic literature review (SLR). The systematic literature review method used in this research is the PRISMA method. Article search, article extraction, and article classification using the Watase UAKE application. The article search was conducted online using two (2) database sources, namely Scopus (Q1-Q4) and Semantic Scholar. The review showed that social media has the potential to be an effective virtual public sphere in health education. This platform can be used to. Increase awareness and understanding of health Provide information and support for individuals in need, strengthen community participation in health education, However, social media also has some limitations in supporting health education. These limitations include: Disinformation and misinformation, Polarization of opinion Conflict of interest. In this review concludes that social media can be a valuable tool for health education. However, it is important to be aware of its limitations and take steps to overcome them.